The Pro12Ala Polymorphism of PPAR-γ Gene Is Associated with Sepsis Disease Severity and Outcome in Chinese Han Population - Guoda Ma; Haiyang Wang; Guixi Mo; Lili Cui; You Li; Yiming Shao; Xin Liu; Yuliu Xie; Jia Li; Jiawu Fu; Hua Tao; Bin Zhao; et al. (PPAR Research)
Peroxisome proliferator-activated receptor-γ (PPAR-γ) is a ligand-binding nuclear receptor, and its activation plays a prominent role in regulating the inflammatory response. Therefore, PPAR-γ has been suggested as a candidate gene for sepsis. In the present study, we investigated the association between the Pro12Ala polymorphism of PPAR-γ and sepsis in a Han Chinese population. A total of 308 patients with sepsis and 345 healthy controls were enrolled in this study. Genotyping was performed using the polymerase chain reaction-ligation detection reaction (PCR-LDR) method. No significant differences were detected in the allele and genotype distributions of the PPAR-γ Pro12Ala SNP between septic patients and controls (P=0.622 for genotype; P=0.629 for allele). However, stratification by subtypes (sepsis, septic shock, and severe sepsis) revealed a statistically significant difference in the frequency of the Ala allele and Ala-carrier genotype between the patients with the sepsis subtype and the healthy controls (P=0.014 for allele and P=0.012, for genotype). Moreover, significant differences were found in the frequency of the Ala allele and genotype between the sepsis survivors and nonsurvivors (all P=0.002). In the survivors, the PPAR-γ Pro12Ala genotype was significantly associated with decreased disease severity and recovery time (all P<0.001). Thus, genetic polymorphism is thought to play a role in the development and outcome of sepsis.